Optimum organ volume ranges for organs at risk dose in cervical cancer intracavitary brachytherapy - Zahra Siavashpour; Mahmoud Reza Aghamiri; Ramin Jaberi; Hamid Reza Dehghan Manshadi; Reza Ghaderi; Christian Kirisits (Journal of Contemporary Brachytherapy, 2016)
Purpose: To analyze the optimum organ filling point for organs at risk (OARs) dose in cervical cancer high-dose-rate (HDR) brachytherapy. Material and methods : In a retrospective study, 32 locally advanced cervical cancer patients (97 insertions) who were treated with 3D conformal external beam radiation therapy (EBRT) and concurrent chemotherapy during 2010-2013 were included. Rotterdam HDR tandem-ovoid applicators were used and computed tomography (CT) scanning was performed after each insertion. The OARs delineation and GEC-ESTRO-based clinical target volumes (CTVs) contouring was followed by 3D forward planning. Then, dose volume histogram (DVH) parameters of organs were recorded and patients were classified based on their OARs volumes, as well as their inserted tandem length. Results : The absorbed dose to point A ranged between 6.5-7.5 Gy. D 0.1cm ³ and D 2cm ³ of the bladder significantly increased with the bladder volume enlargement (p value < 0.05). By increasing the bladder volume up to about 140 cm3, the rectum dose was also increased. For the cases with bladder volumes higher than 140 cm3, the rectum dose decreased. For bladder volumes lower than 75 cm3, the sigmoid dose decreased; however, for bladder volumes higher than 75 cm3, the sigmoid dose increased. The D 2cm ³ of the bladder and rectum were higher for longer tandems than for shorter ones, respectively. The divergence of the obtained results for different tandem lengths became wider by the extension of the bladder volume. The rectum and sigmoid volume had a direct impact on increasing their D 0.1cm ³ and D 2cm ³, as well as decreasing their D 10 , D 30 , and D 50 . Conclusions : There is a relationship between the volumes of OARs and their received doses. Selecting a bladder with a volume of about 70 cm3 or less proved to be better with regards to the dose to the bladder, rectum, and sigmoid.